Automatic camera calibration and sensor registration of a multi-sensor fringe measurement system using hexapod positioning - Metzner, Sebastian; Hausotte, Tino (Proc. SPIE 11056, Optical Measurement Systems for Industrial Inspection XI, 1105616, 2019)
For the requirements of newly developed production processes like sheet bulk metal forming a previously developed measuring method exists for dimensional measurement of these manufactured parts. The presented multi-sensor approach allows the combination of several fringe projection sensors with different measurement resolutions and ranges to meet the requirements of the new production technology. The measurement setup includes a high precision hexapod to position the investigated workpiece inside the measuring volume. The measurement devices utilized are high precision fringe projection systems with 17 µm lateral and 1 µm vertical resolution. An additional overview sensor captures the whole measurement range of the hexapod. This paper presents two approaches that can be used for camera calibration and sensor registration of the fringe projection systems in a global coordinate system. A speckle pattern and a random dot pattern are placed on the hexapod to calculate the intrinsic parameters of the sensor camera and extrinsic parameters of the fringe sensor in one single step. To obtain metric lengths with the calibration process, a defined scale is included additionally on the pattern. The calibration process is executed by an automatic and random movement of the hexapod in the recording area of the sensors. Measurements show a direct transferability from the camera to the sensor coordinate system. This allows the measurement datasets to be directly merged together without the use of a separate registration routin
Keywords: Calibration; Speckle pattern; Image registration; Optical flow; Feature extraction

Bestimmung des Brechungsindex des Schmiermittels Beruforge 152DL unter Verwendung eines dafür entwickelten Dünnschichtnormals - Metzner, Sebastian; Reuter, Tamara; Wirthmann, Elisa; Hausotte, Tino (20. GMA/ITG-Fachtagung Sensoren und Messsysteme 2019, 2019)
Für eine Messung von blechmassivumgeformten Bauteilen möglichst nahe am Fertigungsprozess spielen systematische Abweichungen durch den darauf noch verbliebenen Schmierstoff eine signifikante Rolle. Die erwartete Schichtdicke dieses Schmierstoffs liegt bei den betrachteten Bauteilen in einem Bereich von unter 35 μm. Für die Bestimmung des Brechungsindex des Schmiermittels und somit die Auswirkungen des Schmierstoffs auf die interferometrische Messung, wird ein Dünnschichtnormal vorgestellt, welches in einem Bereich von 6 bis 100 μm einen kontinuierlichen Messbereich abbildet. Mit dem eingesetzten Messverfahren, einer koaxialen interferometrischen Schichtdickenmessung, können so in verschiedenen Abständen die optische Dicke bestimmt werden. Daraus lässt sich im Anschluss der Brechungsindex näherungsweise bestimmen. Zudem können die Abweichungen der angezeigten Schichtdicke bei bekanntem Brechungsindex nun bewertet werde

Characterization of the single point precision of steel gear wheel measurements using tactile coordinate measurement machines in scanning mode - Müller, Andreas; Metzner, Sebastian; Hausotte, Tino (20. GMA/ITG-Fachtagung Sensoren und Messsysteme 2019, 2019)
The framework of the single point uncertainty developed at the Institute of Manufacturing Metrology (FMT) presents a methodology to determine and evaluate the local measurement uncertainty for a measurement setup by local comparison of a measurement series with an associated reference geometry. This approach, which was originally developed and optimized for the processing of complete areal measurements of work pieces, was now also extended to line scans found in dimensional testing using tactile coordinate measurement machines (CMM). Target of the investigation are straight-toothed steel gear wheels, which can be dimensionally characterized by both helix and profile scans using a CMM in scanning mode in combination with a rotatory stage. The modification of the single point uncertainty framework in order to determine the single point precision of repeated gear wheel measurements was implemented successfully but the test setup also yielded abnormally high random measurement errors, which could not fully be explained within our examination
Keywords: gear wheel; tactile coordinate measurement; single point precision; scanning mode

Evaluation of reflection properties of sheet bulk metal formed parts by pixel wise analysis of camera images provided for triangulation measurement - Metzner, Sebastian; Ramesh, Rahul; Müller, Andreas; Hausotte, Tino (ITG-Fachbericht 281 Sensoren und Messsysteme, 2018)
Dimensional measurements with optical measuring systems often involve challenges for reflective surfaces. Especially, measuring systems which use structured light for measurement generate overexposed regions in reflective areas of the workpiece. The present work describes a possibility to extend a point cloud, taken by a fringe projection system, with a quality value to provide information concerning the uncertainty of the measured points and the reflection properties of the surface. This quality value is based on a measurement of the workpiece with passive triangulation. This allows in addition a subsequent extension of the initial measurement with the fringe projection system with the point cloud of the passive triangulation.<br

Evaluation on influences of thin lubricant on fringe projection measurements - Metzner, Sebastian; Reuter, Tamara; Hausotte, Tino (Optical Technology and Measurement for Industrial Applications, 2019)
Sheet bulk metal forming processes pose challenges for fringe projection systems, as the lubricant applied for forming could influence the measurement result. The lubricant layer has an expected film thicknesses smaller than 35 μm after the forming process. This paper presents an approach for the measurement of the lubricant layer influence on fringe projection measurements. The lubricant (Beruforge 152DL) used for the forming process and investigated in this paper has special characteristics like a water-based basic fluidity and wax particles for friction reduction as component of the liquid. A newly developed fluid film thickness standard represents the film thickness in a continuous range. This paper shows the impact on the standard deviation of the measurement results and a significant deviation of the detected surface on fluid film thickness standard with the applied lubricating film.
Keywords: fringe projection system; lubricant measurement; sheet bulk metal forming

Extension of the registration possibilities and determination of the positioning precision of a multi-scale fringe projection system - Metzner, Sebastian; Hausotte, Tino (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
For providing holistic and complete dataset of sheet bulk metal-formed parts, an optical detection with a fringe projection system is useful. By combining several sensors with varying measuring ranges, the workpiece is captured with adapted spatial resolution depending on the forming zone and geometric requirements. The sensors are registered by a two-dimensional point calibration and registration process. The registration process has already been shown in.1 In this article, the calibration procedure is transferred to the measurement setup with three fringe projection sensors with different measurement resolution. A calibration plate with dot patterns is applied to the positioning unit, which is a high precision hexapod in this set-up. This extended calibration plate allows a continuous control of the registration quality as the sensors are able to capture the calibration plate at any time. For determining the positioning accuracy of the hexapod, a procedure following the DIN EN ISO 10360-3 procedure with three spheres mounted on the hexapod was investigated. Therefore the hexapod was fixed at a coordinate measuring machine Zeiss UPMC 1200 and moved in all 6 degrees of freedom. After each movement, the spheres were measured with a probe, which allows the absolute position precision to be calculated. Comparison of the measurements with the specified translation and rotation movement of the hexapod show a positioning precision of less than 10 μm in the positioning directions x and y.
CRIS-Team Scopus Importer:2020-06-09
Keywords: coordinate measurement; hexapod; multi-scale multisensor measurement system; position precision

Fringe projection profilometry in production metrology: A multi-scale comparison in sheet-bulk metal forming - Hinz, Lennart; Metzner, Sebastian; Müller, Philipp; Schulte, Robert Karl; Besserer, Hans-Bernward; Wackenrohr, Steffen; Sauer, Christopher; Kästner, Markus; Hausotte, Tino; Hübner, Sven; Nuernberger, Florian; Schleich, Benjamin; et al. (Sensors, 2021)
Fringe projection profilometry in combination with other optical measuring technologies has established itself over the last decades as an essential complement to conventional, tactile measuring devices. The non-contact, holistic reconstruction of complex geometries within fractions of a second in conjunction with the lightweight and transportable sensor design open up many fields of application in production metrology. Furthermore, triangulation-based measuring principles feature good scalability, which has led to 3D scanners for various scale ranges. Innovative and modern production processes, such as sheet-bulk metal forming, thus, utilize fringe projection profilometry in many respects to monitor the process, quantify possible wear and improve production technology. Therefore, it is essential to identify the appropriate 3D scanner for each application and to properly evaluate the acquired data. Through precise knowledge of the measurement volume and the relative uncertainty with respect to the specimen and scanner position, adapted measurement strategies and integrated production concepts can be realized. Although there are extensive industrial standards and guidelines for the quantification of sensor performance, evaluation and tolerancing is mainly global and can, therefore, neither provide assistance in the correct, application-specific positioning and alignment of the sensor nor reflect the local characteristics within the measuring volume. Therefore, this article compares fringe projection systems across various scale ranges by positioning and scanning a calibrated sphere in a high resolution grid.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Coordinate metrology; Fringe projection; Production metrology; Sheet-bulk metal forming

Ganzheitliche dimensionelle Messung von blechmassivumgeformten Bauteilen. - Metzner, Sebastian; Hausotte, Tino; Loderer, Andreas (Technisches Messen, 2017)
Due to recent developments in sheet-bulk metal forming processes, holistic and production related measuring systems are required which provide reliable results from all relevant formed part features. The multi scale multisensor approach, which combines several sensors of different measuring methods, resolutions and ranges, accomplishes the requirements of the new production technology. A specially developed methodological procedure allowed a structured system development with different goals as an interim result. The resulting multi scale multisensor measurement system, based on three different fringe projection sensors, allows dimensional measurements of characteristicswhose size exceeds themeasuring range of one single senso
Keywords: Production-oriented part inspection; multi scale fringe projection; multisensor measurement system.

Holistic dimensional measurement of sheet-bulk metal formed parts - Metzner, Sebastian; Hausotte, Tino (Proceedings Vol. 10819 - Optical Metrology and Inspection for Industrial Applications V, 2018)
Due to recent developments in sheet-bulk metal forming processes, holistic measuring systems are required which provide reliable results for the measurement of all relevant formed part features. The presented multi scale multisensor approach, which combines several fringe projection sensors of different measuring resolutions and ranges, accomplishes the requirements of the new production technology. Calibration of the single measurement systems to a global coordinate system is realized with a specially developed calibration object. A high-precision hexapod positions the calibration object and the workpiece within the measuring range. The result is a holistic dimensional measurement for characteristics whose size exceeds the measuring range of a single sensor. It is also shown that the distance of the measurement sensor to the suface of the measurement object is relevant for the uncertainty of the obtained point cloud. By positioning the workpiece in the focus of camera of the fringe projection system, the standard deviation of the measured point cloud can be significantly reduce
Keywords: multi scale fringe projection; multisensor measurement system; hexapod

Interferometrische Messung der Positioniergenauigkeit und Verkippung einer Hexapod-Positioniereinheit - Metzner, Sebastian; Knippen, Winand; Hausotte, Tino (Aktuelle Entwicklungen im Bereich der Umformtechnik, 2020)

Local histogram equalization and homomorphic filtering to improve wide-angle stereo disparity computation - Metzner, Sebastian; Ramesh, Rahul; Hausotte, Tino (Forum Bildverarbeitung 2018, 2018)
Dimensional measurements of reflective surfaces are often challenging for optical measurement systems. The use of structured light causes overexposure of the reflective regions, resulting in an incomplete measurement. Stereo vision is an effective alternate to optical measurements. Image rectification and disparity map computation steps are used to generate a 3D point cloud which can be used for dimensional measurements. When the stereo vision setup requires cameras at wide angles to the surface normal, the image pairs are affected by varying illumination, once again resulting in bad disparity. In this paper different image processing possibilities are examined at the example of a sheet-bulk metal formed workpiece to obtain an improved disparity map of the overexposed areas of the data set. A newly developed local histogram equalization method improves the disparity map for stereo vision calculations with wide-angle camera setups.<br
Keywords: wide-angle stereo vision; image processing; disparity computation

Measurement of the Beruforge 152DL thin-film lubricant using a developed thin-film thickness standard - Metzner, Sebastian; Reuter, Tamara; Hausotte, Tino (Journal of Sensors and Sensor Systems, 2020)
Systematic deviations due to remaining lubricant on the workpiece have a significant influence on the measurement of sheet-bulk metal formed parts. The expected layer thickness for the workpieces after the forming process is less than 35 µm. For the determination of the refractive index of the lubricant and thus the effects of the lubricant on optical measurement techniques, a lubricant thin-film thickness standard was developed which represents a continuous measuring range from 6 to 100 µm. To determine the refractive index, the thin-film thickness standard was measured with a coaxial interferometric measurement system in various thickness ranges. Due to the knowledge of the optical and the geometrical path length, the refractive index can then be determined approximately. In addition, an XY stage was used to scan the entire thin-film area of the standard. The measurement setup in a temperature box allows for determining the effects of temperature changes on the optical properties of the lubricant.<br

Separation of locally determined work piece deviations and measurement uncertainties for structured-light scanning of customized polymer gear wheels - Müller, Andreas; Metzner, Sebastian; Hausotte, Tino; Schubert, Dominik; Drummer, Dietmar (20. GMA/ITG-Fachtagung Sensoren und Messsysteme 2019, 2019)
During the manufacturing of work pieces, geometrical deviations from the intended nominal geometry of the designer are inevitable. The procedure of conformance testing defined in ISO 14253-1:2018-07 is used to ensure the function of a work piece by verifying the geometrical compliance with pre-defined tolerance specifications. Depending on the measurement setup used for the validation step and the accuracy of the manufacturing process, it is possible that the measurement uncertainty is large enough to have a significant influence on the conformance evaluation. The measurement uncertainty for optical measurement systems is influenced by the surface properties of the test specimen. This contribution aims to demonstrate the complete workflow for the determination of the single point uncertainties for a given measurement task in order to separate the local work piece deviations from the systematic and random components of the measurement uncertainty. It could be shown for a demonstration scenario that different necessary coloring methods of polymer gear wheels, which are required to enable measurements using structured-light scanning, have a measureable influence on the local distribution of the measurement uncertainty. This information could then be used for downstream processes in various use cases, e.g. for the improvement of holistic tolerance simulation models or the improvement of geometrical measurements using weighted regression analysi
Keywords: structured-light scanning; work piece deviations; measurement uncertainty; gear wheel; colored polymer

Strategies for Function-Oriented Optical Inspection of Formed Precision Workpieces - Metzner, Sebastian; Hausotte, Tino; Loderer, Andreas (Sheet Bulk Metal Forming, 2020)
Shorter production times, associated with sheet-bulk metal forming (SBMF), require a demand-adapted monitoring and measurement of the formed geometries. In the present work, a multi-scale and multi-sensor setup was developed to meet these requirements. The difficulty in measuring workpieces formed during SBMF are highly reflective areas with varying demands on the measurement resolution of the functional elements. With the developed measurement setup and the integrated sensors used, the functional elements can be measured with sufficient resolution. The registration of the sensors is done with a specially constructed calibration plate. A parallel kinematic hexapod positioning unit provides six degrees of freedom to precisely position the workpiece in front of the individual measurement sensors. The hexapod is therefore registered in a global coordinate system with the new calibration plate. After the calibration, the measured datasets can be merged together automatically. The rigid connection of the calibration plate to the hexapod enables a more demand-oriented verification of the registration between the individual measurements of the sensors. For overexposure due to directly reflecting areas, it is possible to estimate the quality of each reconstructed data point. A deflectometry system, which is attached to the existing fringe projection sensor, makes it possible to detect strongly directionally reflecting areas and thus provide a holistic reconstruction of the workpiece. The influence of remaining lubricant on the workpiece is simulated by a developed thin film thickness standard. This is to adapt the measuring procedure for reconstructions under harsh conditions in industrial environment. This standard allows the measurement of thin films with the existing optical measurement systems in a range <100 µm. The effects of thin layers of lubricant on the result of the fringe projection measurements show an increasing impact on the measured dataset with increasing layer thickness. With the developed measurement setup, the investigations on the lubricant used and reflective properties, the formed workpieces can be measured at different scale ranges.<br

Verknüpfung von Datensätzen mit unterschiedlicher Auflösung mittels parallelkinematischem Positioniersystem - Metzner, Sebastian; Hausotte, Tino (VDI-Berichte, 2021)